INTEGRATION OF EDAPHIC, TOPOGRAPHIC AND LAND USE FACTORS IN THE ASSESSMENT OF AGRICULTURAL SUITABILITY FOR COCOA CULTIVATION IN NOVO REPARTIMENTO - PA, THROUGH THE APPLICATION OF THE AHP METHOD AND GEOPROCESSING (REMUNOM, 2025)
Cocoa (Theobroma cacao L.) cultivation is of great importance to the economy of the state of Pará, especially for municipalities along the Trans-Amazonian Highway and the Southeast region, such as Novo Repartimento in Pará. Therefore, identifying areas suitable for cultivation and for sustainable expansion is essential. Given the above, the objective of this research was to evaluate the expansion potential for cocoa cultivation in the municipality by integrating edaphic, topographic, and land use and occupation parameters, using the Hierarchical Process Analysis (HPA) methodology in a GIS environment. Thematic slope maps were generated from a digital elevation model (DEM), a land use and land cover map obtained from MapBiomas, and a raster containing soil classification was generated from vector data containing soil pedology in the region. After obtaining the rasters containing each criterion, a score was assigned to the subcriteria from 1 to 4, with 4 representing the highest potential and 1 the lowest. After this reclassification, the data for each raster were normalized so that they ranged from 1 to 4. After these procedures, a weighted average was applied to the evaluated criteria. The results indicated a predominance of areas classified as having medium to high agricultural potential, with a total of 57.84%. The highest concentration of suitability was located in the Southeast, Northwest, and Central regions. Given the above, it can be concluded that the integrated application of the AHP method and GIS is an efficient tool to support agricultural planning and the sustainable expansion of cocoa farming in the studied municipality.